2017
DOI: 10.1111/area.12408
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the interview transcript: Identifying spatial policy areas from daily working practices

Abstract: An interview transcript can be a rich source of geographical references whose potential are not always fully realised in their conventional analysis. Geo-referencing techniques can be used to assign a spatial footprint to place names, adding value to these data and allowing the geographic information within them to be exploited when coupled with GIS technology. This paper discusses a method of analysing and visualising interview transcripts in order to understand the spatial extent of public policy practitione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…It is within this climate of joint working between LAs that, in South Wales, two city-regions have been created via LA collaboration and this in turn has led to North Wales seeking a growth deal for itself. The 'region' of North Wales itself also reflects a complicated geography, highlighted by The Wales Spatial Plan (Welsh Government, 2008), which identified the different regions of Wales as having extremely 'fuzzy boundaries', with stretched-out and relational public policy interventions occurring in some instances (Orford & Webb, 2018). 'North Wales' stretches into what has been called the 'Deep Rural' (Wales Rural Observatory, 2009) of mid-Wales; for example, where southern Gwynedd (Meirionnydd) blurs into the mid-Wales LAs of Powys and Ceredigion.…”
Section: Making Interstitial Spaces: the Growth Deal Approachmentioning
confidence: 99%
“…It is within this climate of joint working between LAs that, in South Wales, two city-regions have been created via LA collaboration and this in turn has led to North Wales seeking a growth deal for itself. The 'region' of North Wales itself also reflects a complicated geography, highlighted by The Wales Spatial Plan (Welsh Government, 2008), which identified the different regions of Wales as having extremely 'fuzzy boundaries', with stretched-out and relational public policy interventions occurring in some instances (Orford & Webb, 2018). 'North Wales' stretches into what has been called the 'Deep Rural' (Wales Rural Observatory, 2009) of mid-Wales; for example, where southern Gwynedd (Meirionnydd) blurs into the mid-Wales LAs of Powys and Ceredigion.…”
Section: Making Interstitial Spaces: the Growth Deal Approachmentioning
confidence: 99%
“…It is within this climate of joint working between LAs that, in South Wales, two city regions have been created via LA collaboration and in turn this has led to North Wales seeking a Growth Deal for. The 'region' of North Wales also reflects a complicated geography, highlighted by The WSP (Welsh Government, 2008), which identified the different regions of Wales as having extremely 'fuzzy boundaries', with stretchedout and relational public policy interventions occurring in some instances (see Orford and Webb, 2018). 'North Wales' stretches into what has been called the 'Deep Rural' (Wales Rural Observatory, 2009) of mid-Wales; for example, where southern Gwynedd (Meirionnydd), blurs into the mid-Wales LAs of Powys and Ceredigion.…”
Section: Devolved Regions In Action: Placing North Walesmentioning
confidence: 99%
“…Yet, as discussed below, both quantitative and qualitative GIS offer considerable potential for such policy making and analysis, examples of which are highlighted in the next section As with any methodological field, GIS techniques, thinking and capabilities continue to evolve, opening up new opportunities for rich spatial insights into social policy issues. Increasingly, for example, more traditional quantitative GIS representations of containerised Cartesian spaces are being challenged through attempts to characterise the relationship between places by mapping flows of data -trade, people, finance, information and so on -rather than displaying static representations of place (Orford and Webb, 2017). Most commonly, flow maps are utilised to map commuting patterns of workers, showing how many people travel from home to work (Rae, 2016) in order to understand the functional geographies of cities and regions -Figure 9.1.…”
Section: Why Is Gis a Useful Tool For Spatial Social Policy Analysis?mentioning
confidence: 99%
“…Finally, a slightly different example of qualitative GIS in social policy research comes from Orford and Webb (2017) and their mapping of social policy areas identified from the daily working practices of public policy practitioners in Wales. Here practitioners were interviewed in depth about their daily working lives and were encouraged to talk about the places that were significant in their activities.…”
Section: Case Studies Of Indicative Examplesmentioning
confidence: 99%